Comparison of the adhesive remnant index and shear bond strength of orthodontic brackets using acid etch versus Er:YAG laser treatments. (30th September 2019) - Mirhashemi, Amirhossein; Sharifi, Nastaran; Kharazifard, Mohammad Javad; Jadidi, Hanieh; Chiniforush, Nasim
Abstract: Among the different methods of etching in orthodontic procedures, phosphoric acid etching is the most widely used method with the best bonding affinity, but it has its own drawbacks. To overcome these shortcomings new methods have been developed, among which laser-based approaches are of great importance due to ease of use and few side effects. In this study, the bonding strength of an Er:YAG laser was compared with those of acid etching and self-etching primers for the bonding of orthodontic brackets. One hundred teeth were randomly divided into five groups to evaluate the properties of each different adhesive system: acid etching, self-etching, Er:YAG laser etching, Er:YAG laser etching  +  self-etching and Er:YAG laser etching  +  acid etching. Adhesive remnant index (ARI) scores and shear bond strength (SBS) data were analyzed using the Kruskal–Wallis test and ANOVA test, respectively. The results of the ANOVA test implied that a significant difference exists between the mean SBS values of the study groups, where the acid-etched groups have the highest bond strengths. The results show that a statistically meaningful difference exists between the ARI scores of the groups. The results of this study imply that acid etching is the best etching method with regards to bonding strength, but the Er:YAG laser has acceptable bonding strength.